The Feminist XResistance Project: Reflections and Commentary - Ariel, Galit; Bhandari, Aparajita; York-Bertram, Sarah; Hopkins, Kacie G. (Atlantis, 2024)
On May 31, 2023, we showcased the Feminist XResistance project at the Women and Gender Studies et Recherches Féministes (WGSRF) conference under the apt thematic “Take Back the Future.” The project started on July 9, 2022, when a group of international, interdisciplinary, early career feminist scholars convened on Zoom for the Feminist Digital Methods (FDM) Drop-in Virtual Lab hosted by York University’s Centre for Feminist Research (CFR). The drop-in took place two weeks after the United States Supreme Court overturned the constitutional right to an abortion and became a digital space to express our fears and anger over rising gender essentialist fascism, worries about the future, and to imagine feminist digital methods for resistance. In this reflection and commentary, we share our observations and processes for the Feminist XResistance project, starting with our first exploratory workshop, our co-creative analysis and outputs, the development of our AR installation, and, finally, our conclusions and insights.